COLLEGE CONVERSION INTO COVID-19 QUARANTINE CENTER: READINESS OF STUDENTS TO GO BACK TO COLLEGE - Mwende, Rachael; Mramba, Caroline; Mutonga, Dominic; Nchogu, Rhoda; Ogendo, Marsellah; Ngechu, Dorcas; Mramba, Garama; Mwema, Jeniffer; Miriti, Rita; Ogada, Japheth; Barawa, Winnie (African Journal of Education and Practice, 2020)
Purpose: The aim of the study was to assess students' readiness to go back to college after closure due to COVID-19. Methodology: The study used a descriptive cross-sectional design which was done at KMTC-Mombasa Campus. Participants (Students) were selected using multi stage sampling and sample size determination was done using Fischer's statistical formula at a confidence level of (p=95%), n=253. Data was obtained using a structured questionnaire through online surveys and focused group discussions via online platform. Data analysis was done using SPSS and Excel then results presented using tables and narrations. Results: 76.7% (194) of the respondents were ready to get back to college immediately while 23.3% (59) were willing to resume studies later. The main reason for respondents wanting to go back to college immediately was to finish school (n=60). 67.8 % (40) of the respondents who wanted to go back later feared contracting COVID-19. 78% (175) of respondents were aware that college had been used as quarantine center yet they were still ready to go back to college immediately. Unique contribution to theory, practice and policy: The closure of learning institutions globally during the COVID-19 pandemic is unprecedented. Readiness of college students to resume studies in an institution used as a quarantine centre for clients suspected of having a highly infectious disease has not been examined in literature. The findings of this study are useful to policy makers and leaders in education sector as normalcy resumes and learning institutions are opened.